1970
DOI: 10.1139/v70-254
|View full text |Cite
|
Sign up to set email alerts
|

Application of proton magnetic resonance to rotational isomerism in halotoluene derivatives. II. α,α,2,4,6-Pentachlorotoluene

Abstract: At temperatures below -40 "C the proton magnetic resonance of a,a,2,4,6-pentachlorotoluene in toluene-d8 or methylcyclohexane is an ABX spectrum where X is the methine proton. The C-H bond of the dichloromethyl group lies in the plane of the ring and its proton couples to one ring proton only. As the temperature increases the mean lifetime before interconversion of the "mirror image" isomers decreases and at 70 "C the proton spectrum is A2X. A density matrix formalism is used to calculate the line shape as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1970
1970
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…In perchlorobutadiene the 100 MHz proton spectrum consisted of a tightly coupled ABC spectrum at 30 OC. However, in toluene-d8 the 100 MHz proton spectrum is ABX, very similar to the spectrum for PCT at -40 OC (1). It was previously shown that the intrinsic temperature dependence of the internal ring proton shift of PCT in toluene-d8 can and must be found in order to obtain reliable exchange rates from fitted spectra.…”
Section: ( 2 ) Proton Magnetic Resonance Spectramentioning
confidence: 55%
See 3 more Smart Citations
“…In perchlorobutadiene the 100 MHz proton spectrum consisted of a tightly coupled ABC spectrum at 30 OC. However, in toluene-d8 the 100 MHz proton spectrum is ABX, very similar to the spectrum for PCT at -40 OC (1). It was previously shown that the intrinsic temperature dependence of the internal ring proton shift of PCT in toluene-d8 can and must be found in order to obtain reliable exchange rates from fitted spectra.…”
Section: ( 2 ) Proton Magnetic Resonance Spectramentioning
confidence: 55%
“…The spectra themselves are very similar to those of PCT presented in ref. 1. Table 1 gives the spectral parameters in the region of slow exchange.…”
Section: Results and Discussion ( I ) Spectral Parameters At Low Exchmentioning
confidence: 99%
See 2 more Smart Citations
“…From studies on a,a,2,6-tetrachloro-and a,a,2,6-pentachlorotoluene (6,10) it is known that this five-bond coupling is conformation dependent. Thus in 2, s 0.5 1iz whereas J>nHx < 0.10 HZ, indicating a preponderant o electron contribution to J :~~~~~.…”
Section: Tile Long-range Proton-proton Couplingsmentioning
confidence: 99%